White matter abnormalities in the amputation variant of body integrity dysphoria. (June 2022) - Saetta, Gianluca; Ruddy, Kathy; Zapparoli, Laura; Gandola, Martina; Salvato, Gerardo; Sberna, Maurizio; Bottini, Gabriella; Brugger, Peter; Lenggenhager, Bigna
Abstract: "Body integrity dysphoria" (BID) is a severe condition affecting nonpsychotic individuals. In the amputation variant of BID, a limb may be experienced as not being part of the body, despite normal anatomical development and intact sensorimotor functions. We previously demonstrated altered brain structural (gray matter) and functional connectivity in 16 men with BID with a long-lasting and exclusive desire for left leg amputation. Here, we aimed to identify, in the same sample, altered patterns of white matter structural connectivity. Fractional anisotropy (FA), derived from diffusion tensor imaging data, was considered as a measure of structural connectivity. Results showed reduced structural connectivity of: (i) the right superior parietal lobule (rSPL) with the right cuneus, with the superior occipital and with the posterior cingulate gyri, (ii) the pars orbitalis of the right middle frontal gyrus (rMFGOrb) with the putamen, and (iii) the left middle temporal gyrus (lMTG) with the pars triangularis of the left inferior frontal gyrus. Increased connectivity was found between the right paracentral lobule (rPLC) and the right caudate nucleus. By using a complementary method of investigation, we confirmed and extended previous results from the same sample of individuals with BID, showing structural alterations between areas tuned to the processing of the sensorimotor representations of the affected leg (rPCL), and to higher-order components of bodily representation such as the body image (rSPL) and visual processing. Alongside this network for bodily awareness, other networks such as the limbic (rMFGOrb) and the mirror (lMTG) systems showed alterations in structural connectivity. These findings consolidate current understanding of the neural correlates of the amputation variant of BID, which might in turn guide diagnostics and rehabilitative treatments.